VdPAT1 encoding a pantothenate transporter protein is required for fungal growth, mycelial penetration and pathogenicity of Verticillium dahliae - Kamau, Stephen Mwangi; Li, Yongtai; Sun, Tiange; Liu, Feng; Zhu, Qian-Hao; Zhang, Xinyu; Sun, Jie; Li, Yanjun (Frontiers in Microbiology, 2025)
IntroductionThe soil-borne vascular fungus Verticillium dahliae is a phytopathogenic fungus known to attack cotton crop causing Verticillium wilt. In previous study, we identified a pantothenate transporter gene (VdPAT1) in V. dahliae which can be induced by root exudates from a susceptible cotton variety.MethodsIn this study, we generated VdPAT1 deletion mutants and complementary strain via homologous recombination by a PEG-mediated transformation method and used for the gene functional characterization.Results and discussionThe VdPAT1 deletion mutants displayed reduced colony growth, melanin production, spore yield and germination rate, showed abnormal mycelial branching and decreased ability of mycelial penetration and utilization of nutrients (carbon, amino acids and vitamin), leading to a lower pathogenicity. Comparative transcriptome analysis of wild-type and mutant strain cultivated on sterilized carboxymethyl cellophane membranes found that the amino sugar and nucleotide sugar metabolism pathway, which was related to chitin synthesis and degradation as well as UDP-glucose synthesis, was the most significantly down-regulated pathway in VdPAT1 deletion mutant. Chitin and β-1,3-glucan content determination found that the chitin content in VdPAT1 deletion mutants was significantly lower, while β-1,3-glucan content was higher than that of wild-type and complementary strains. The ratio change of chitin and β-1,3-glucan content in VdPAT1 deletion mutants might lead to abnormal branching of mycelium, resulting in the reduced penetration ability of V. dahliae. The decreased chitin content in VdPAT1 mutants impaired the fungal cell wall integrity, leading to their increased sensitivity to external stresses.ConclusionTogether, the results demonstrated that VdPAT1 is required for growth, development, resistance to external stresses, mycelial penetration and pathogenicity of V. dahliae.